Asymmetric Crying Face in a Newborn with Isotretinoin Embryopathy. Issue 6 (21st May 2012) - Sarici, Dilek; Akin, Mustafa Ali; Kurtoglu, Selim; Uzum, Kazim; Kiraz, Aslihan
<x xml:space="preserve">Abstract</x> Abstract: We report a newborn with asymmetric crying face and other anomalies whose mother had taken isotretinoin during the first month of pregnancy. We hypothesize that asymmetric crying face is a finding of retinoic acid embryopathy and results from the intrauterine effects of retinoic acid on the development of the depressor anguli oris muscle or the mandibular branch of the facial nerve.